Analysis of failure initiation in corroded cast iron pipes under cyclic loading due to formation of through-wall cracks. (September 2019) - Jiang, Rui; Rathnayaka, Suranji; Shannon, Benjamin; Zhao, Xiao-Ling; Ji, Jian; Kodikara, Jayantha
Abstract: The major factors contributing for the longitudinal failures in large-diameter cast iron water pipes are identified as corrosion and internal water pressure. Evidence of deteriorating pipeline integrity due to fluctuations of internal pressure loading was reported. This study aims to investigate the fatigue resistance of cast iron pipes and to identify the pipes in a water network that are at high risks of fatigue damage. Stress-controlled fatigue tests were conducted on coupons prepared from exhumed cast iron pipes. A correlation between tensile fatigue stress and cycles to failure was developed based on experimental results. A methodology was proposed to identify critical factors for initiating a through-wall crack in cast iron water pipe considering the impact of fatigue. A sensitivity analysis was conducted with relevant factors, and the relative impact of those factors to cause a premature failure was assessed. The operating pressures and stress ratios caused by pressure transients and long-term soil corrosion rate were identified as the key contributing factors for severe fatigue damage. Highlights: SN curves were developed by fatigue tests for CI pipes and the results were compared with published data from research literature The results indicate that fatigue may initiate cracks at critically corroded patches prior to limit state failure. Fatigue damage tends to be more severe in networks with high operating pressures, low stress ratios due to transient events and pipes with low tensile strength. Ageing CI pipes buried in pressure zones prone to pressure transients or /and frequent bursts may require additional condition assessment to assess the risk of fatigue damage.